SARS-CoV-2 gamma variant and chronic arterial insufficiency due to late arterial thrombosis - Pereira de Godoy, Jose Maria; Marum, Guilherme; Amorim, Henrique; Orate Menezes da Silva, Mariana; Cordeiro da Silva, Fernanda (International Journal of Health Sciences, 2022)
The current evidence suggests a state of hypercoagulability as one of the sequelae of hyperinflammation. Thus, it is an important pathogenic mechanism that contributes to increase the mortality caused by COVID-19. The aim of the present study is to report chronic arterial insufficiency after post-thrombosis in the same arteries 32 days later, as a sequel after severe acute respiratory syndrome coronavirus 2 P.1. After the 2nd day of discharge, she had a lot of pain in her left and limiting leg and was referred to the vascular service. The patient was evaluated by vascular surgery who underwent a clinical diagnosis of Rutherford II.A arterial thrombosis and underwent arteriography of the limb that revealed thrombosis of the anterior, posterior, and fibular arteries in the middle third and the plantar arch was not contrasted. She underwent emergency embolectomy with selective isolation of the tibial arteries.